2020
DOI: 10.4081/hpr.2020.8929
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ attitudes regarding the disclosure of medical errors: A qualitative study

Abstract: The experiences of physicians’ errors could affect their professional practice. The aim of study was to explore physicians’ experiences of medical errors and its consequences. This was a qualitative study in which ten Brazilian physicians were selected through purposive sampling. The data were collected via semistructured interviews and analyzed through principles derived of the phenomenological method. The interview topics were around how the error occurred in their practice, its process of disclosure and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Even though MEs were known to the physicians, majority of the respondents were unaware of the theoretical concept and philosophy. Similarly, a study conducted in Brazil reported that physicians considered MEs as a tool to confirm what theory talks about this topic ( 49 ). Similarly, where physicians are engaged in managing a lot of patients, they experience a paradox to conceptualize the concept of MEs.…”
Section: Discussionmentioning
confidence: 97%
“…Even though MEs were known to the physicians, majority of the respondents were unaware of the theoretical concept and philosophy. Similarly, a study conducted in Brazil reported that physicians considered MEs as a tool to confirm what theory talks about this topic ( 49 ). Similarly, where physicians are engaged in managing a lot of patients, they experience a paradox to conceptualize the concept of MEs.…”
Section: Discussionmentioning
confidence: 97%
“…Askarian et al investigated the prevalence of non-reporting MEs in an academic tertiary in Shiraz. They interviewed 283 faculty members, nurses, and medical students regarding the main barriers reported that workload and poor communication among the medical team were the main predisposing factors [1]. Doshmangir et al reported that the medical team did not feel secure and environmental factors were the main predisposing factors of MEs occurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…espite recently increasing attention focused on patient safety, Medical Errors (MEs) frequently occur, but they are not documented or reported most of the time. Studies indicated that MEs are rarely reported [1]. Indeed MEs are a significant threat to patients' safety and a significant challenge that healthcare providers face worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…espite recently increasing attention focused on patient safety, Medical Errors (MEs) frequently occur, but they are not documented or reported most of the time. Studies indicated that MEs are rarely reported [1]. Indeed MEs are a significant threat to patients' safety and a significant challenge that healthcare providers face worldwide [2].…”
Section: Introductionmentioning
confidence: 99%